Health Administration and Patient Satisfaction: Present and Future Challenges - Ahmed Radhi Alali et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Health administration plays a pivotal role in enhancing the quality of care and ensuring patient satisfaction. As healthcare systems become more complex, administrators are tasked with addressing a variety of challenges, including resource allocation, workforce management, and the integration of technology. This review explores the current challenges in health administration related to patient satisfaction and discusses future trends that may reshape the healthcare landscape. Emphasis is placed on strategies to improve the patient experience, including the use of data-driven approaches, personalized care models, and patient-centric policies. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/290 DOI: https://doi.org/10.5281/zenodo.14549444